Providing local self-government bodies with a special administrative regime of resorts - Korchovyi, Roman (Pressing Problems of Public Administration, 2022)
The article discusses the directions of activity of local government bodies in ensuring a special administrative regime for resorts. It has been established that the following are among the most significant features of a resort: the presence of territories with defined boundaries in accordance with established procedures; the presence of natural therapeutic resources within the specified territory; the presence of necessary infrastructure for resort services; official designation as a resort by a competent public authority; classification of the resort territory as a specially protected area; and the presence of a special administrative and legal regime aimed at ensuring the preservation of the resort’s ecosystem and infrastructure. It has been determined that the category of “resort settlement” is a quasi-legal category that has not been defined in current legislation, although it is often used in organizational and managerial documents. It has been established that the status of a “resort settlement” does not contain any restrictions or prohibitions, but rather indicates a certain distinctive feature of a village, town, or city that imposes special requirements on the activities of public authorities and economic entities operating within its territory. The following definition is proposed: a resort settlement is a special type of settlement that encompasses natural therapeutic resources, and whose boundaries and sanitary protection zones have been designated for their preservation. It has been established that the entire territory of a settlement does not necessarily equate to a resort, but the status of a resort settlement denotes the uniqueness of such a settlement or territorial community - the establishment of a special administrative, ecological, and economic regime within its territory. It should be noted that a resort can extend beyond the boundaries of settlements and may even be located within the territory of multiple territorial communities. It has been established that resorts have a specific administrative regime that is determined by the natural conditions, the availability of therapeutic factors on their territory, and the infrastructure. The administrative regime of resort areas primarily involves restrictions on their development. In particular, the construction of new industrial enterprises and other objects on resorts is prohibited, as well as the expansion of existing ones that are not related to satisfying the needs of vacationers and the local population. In addition, the construction of objects that may negatively affect natural therapeutic factors or are not related to resort and residential construction is not allowed. One of the important aspects of the administrative regime of resorts is their sanitary protection, which involves establishing strict sanitary restrictions. It has been established that Ukrainian resorts are classified from an administrative-management perspective according to the type of natural therapeutic resources into resorts of state and local significance. In particular, resorts of state significance are natural territories with particularly valuable and unique natural therapeutic resources that are used for treatment, medical rehabilitation, and disease prevention. Resorts of local significance are natural territories with commonly available natural therapeutic resources that are used for treatment, medical rehabilitation, and disease prevention. The following functions of local government bodies have been analyzed in the respective territories: organizing the activities of the local governance system in the field of ensuring the functioning of resorts; regulating the operation of economic entities within the resort territories within their competence; accounting for natural healing resources and land plots that ensure the functioning of resorts; planning, urban development, and infrastructure development within the competence of local government bodies; preservation, restoration, and improvement of natural healing resources; monitoring the state of natural healing resources; controlling violations of legislation regarding natural healing resources within their competence, and conducting expertise within their competence.